UNIQUE CHARACTERISTICS OF TEACHING FOREIGN LANGUAGES TO YOUNG LANGUAGE LEARNERS - Nurmatov Makhsudbek Muxammadjon o’g’li, (World Scientific Research Journal, 2025)
Abstract: Teaching foreign languages to young learners has special characteristics that make it different from teaching older students. Children learn naturally through play, imagination, and communication rather than through formal grammar study. This article explores the main features that make language instruction for young learners unique and effective. It discusses how cognitive development, motivation, emotional factors, and classroom environment influence learning outcomes. The study also considers practical teaching methods such as storytelling, songs, games, and visual aids that help children stay interested and build language skills in a natural way. Findings suggest that teachers must combine creativity with an understanding of how children think and feel in order to create a positive atmosphere for language learning. The paper concludes that effective teaching of young learners depends on balancing enjoyment, interaction, and structured language practice to support their linguistic and emotional growth.